Siirtyminen nautakarjattomaan maatalouteen - Saksa, P. J.; Aaltio, Sampsa; Kaartinen, Heikki; Ahola, Erkki (Maatalous, 1966)
Keskustelua: Sampsa Aaltio, s. 59 ; Heikki Kaartinen, s. 59-60 ; Erkki Ahola, s. 60-62
Keywords: karjatalous; boskapsskötsel (ekonomi)